Challenges in Implementing Cross-Border Digital Identity Systems for Global Public Infrastructure: A Comprehensive Analysis - Supangkat, Suhono Harso; Firmansyah, Hendra Sandhi; Rizkia, Irma; Kinanda, Rezky (IEEE access, 2025)
The increasing demand for secure and interoperable cross-border digital identity systems has led to challenges in standardization, cybersecurity, and regulatory alignment. Despite advancements in frameworks like eIDAS (EU) and Aadhaar (India), the lack of globally unified standards remains a significant barrier to adoption. This study conducts a systematic literature review (SLR) following the PRISMA framework, analyzing 45 peer-reviewed studies (2018-2024) from Scopus, Web of Science, IEEE Xplore, and Springer. The analysis categorizes challenges into four key domains: technical (interoperability and cybersecurity issues), regulatory (data protection inconsistencies), organizational (financial and governance constraints), and societal (digital inclusion and trust concerns). Findings reveal that 45% of reported challenges stem from interoperability gaps, while 35% result from regulatory fragmentation. Economic disparities further limit digital identity adoption, particularly in developing regions. PPPs are being investigated as a strategic approach to advance blockchain technology and AI-driven identity verification, harmonize regulations, and promote global cooperation to address these issues. This research proposes a scalable and secure digital identity framework, offering actionable recommendations for policymakers, industry stakeholders, and researchers to build inclusive and interoperable global identity ecosystems.